2006
DOI: 10.1037/0012-1649.42.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of perceived adult and peer discrimination among Black, Latino, and Asian American adolescents: Patterns and psychological correlates.

Abstract: This article presents results from a 3-year longitudinal study of the growth patterns and correlates of perceived discrimination by adults and by peers among Black, Latino, and Asian American high school students. Results revealed a linear increase over time in levels of perceived discrimination by adults, whereas perceptions of discrimination by peers remained stable over time. Asian American and non-Puerto Rican Latino adolescents (primarily Dominican) reported higher levels of peer and/or adult discriminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

96
932
11
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(1,044 citation statements)
references
References 68 publications
96
932
11
5
Order By: Relevance
“…This finding is consistent with studies showing that Asian Americans are more likely to experience racial discrimination at school, particularly from peers (Fisher, Wallace, & Fenton, 2000;Greene, Way, & Pahl, 2006;Qin, Way, & Rana, 2008;Rosenbloom & Way, 2004). In addition, the probability of experiencing race-related hate words for Asian Americans has been steady in the last decade at about 0.09.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with studies showing that Asian Americans are more likely to experience racial discrimination at school, particularly from peers (Fisher, Wallace, & Fenton, 2000;Greene, Way, & Pahl, 2006;Qin, Way, & Rana, 2008;Rosenbloom & Way, 2004). In addition, the probability of experiencing race-related hate words for Asian Americans has been steady in the last decade at about 0.09.…”
Section: Discussionsupporting
confidence: 88%
“…These results align with the previous research showing an association between acculturation, acculturative stress, and psychological problems across a variety of ethnic minority and/or immigrant groups (Lopez, Ehly, & Garcia-Vazquez, 2002) as well as with Arab American adolescents (Ahmed et al, 2011). Immigrant or ethnic minority groups who maintain their cultural traditions and values may experience fewer psychological problems because they are able to identify with, and feel a part of, their ethnic community (Greene, Way, & Pahl, 2006). This connection and support may, in turn, provide a buffer to stressors and reduce the likelihood for the manifestation of a psychological disorder.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research supports this assertion and indicates that adolescent youth perceive differential treatment from same-age peers (DuBois, Burk-Braxton, Swenson, Tevendale & Hardesty, 2002;Fisher et al, 2000;. Peer racial discrimination manifests in multiple ways, including intentional or overt social exclusion, teasing, hitting, and unfair treatment based on ethnic group membership (Brown & Bigler, 2005;Chavous et al, 2008;Greene et al, 2006;Rosenbloom & Way, 2004;Verkuyten & Steenhuis, 2005;. The ethnic and racial hierarchies that emerge in classroom-based sociometric research (Graham, Taylor, & Hudley, 1998;Verkuyten & Kinket, 2000), in which ethnic minorities tend to have lower status and are ascribed less favorable characteristics when rated by peers, also suggests that implicit negative group stereotypes operate within same age-peer groups.…”
Section: Racial Climate and Schoolingmentioning
confidence: 92%
“…African American youth can experience school settings in ways that are notably distinct from the experiences of their peers (Fisher, Wallace, Fenton, 2000;Greene, Way, & Pahl, 2006;McLoyd & Steinberg, 1998;Rosenbloom, & Way, 2004). Although children as young as 5 years old are able to notice differential treatment across racial groups (Brown & Bigler, 2004), researchers have found that children's understanding of racial inequality, prejudice and discrimination becomes increasingly complex with age (Brown & Bigler, 2004;Quintana & Vera, 1999).…”
Section: Racial Climate and Schoolingmentioning
confidence: 99%
See 1 more Smart Citation